(3QSGdI GdJUhQ hGdJUOjb ebOeIs - (3GdbhGei, GdTjQGRj, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1050(3g`s
(3ChdgG (B:s
(3CeG HYO ajbhd GdgGQH ef cd LfGH Edi LfGH GdMb GdeYjf eMeO GdeTJgQ HUOQ GdOjf gPg QSGdI eJVefI dJMbjb GdJUhQ hGdJUOjb hJYQjageG cJHJgG HGdJeGS HYV GdNdGf(B...s
(3BNQgG (B:s
...(3hCeG QLhY GdcaGQ Edi Cgd GdHjJ Ydjge GdSdGe aEfge jQLYhf Edi eG UOQhG Yfg efge dCfge UOQhG Yf NdGage hYOGhJge (B...(3jQLY Edi eG UOQ Yfg ef eDef hcGaQs
(3JHUQI GdeDda (B:s
(3CQN UGMH GdCYdGe dhaGJg SfI(B: 1059(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs